2019
DOI: 10.15561/18189172.2019.0603
|View full text |Cite
|
Sign up to set email alerts
|

The effects of tow protocol cold water immersion on the post match recovery and physical performance in well-trained handball players

Abstract: Purpose: The purpose of this study is to compare two cold water immersion (CWI) protocols, continuous and fractionated, to optimize the recovery of Handball players after on recovery from exercise resulting in exercise-induced muscle damage. Material: Ten male Handball players (age: 15 ± 1.4 years, mass index: 67.2 ± 5.1 kg, height: 176.6 ± 7.30) voluntarily participated in the study. After three 90-minute training sessions (average heart rate 160 ± 15.81, 156 ± 5.53 and 156 ± 12.24 bpm) per week, participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…there are a considering changes in level indicators development of the maximum dynamic force of abdominal muscles the press, found mainly a significant improvement, both Men and women of the main groups, and these differences statistically significant (p <0.001). The above is confirmed by the data of (Adel et al 2019;Mokhtar et al 2019;Saddek et al 2020), according to which it was found that during physical exertion, muscle hypertrophy occurs as a result of adaptive-trophic influence (Mukund et Subramaniam 2020;Teplov 1982), which is characterized by an increase in thickness and denser packaging of contractile elements of muscle fiber (Haun et al 2019;Narici et al 1996). Thus, studies (Annesi et al 2005;Belkadi et al 2019;Krivoruchko et al 2018a;Masliak et Mameshina 2018a) indicate that the introduction of functional exercises in the main part of the lesson contributed to a significant improvement in strength abilities of high school students.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…there are a considering changes in level indicators development of the maximum dynamic force of abdominal muscles the press, found mainly a significant improvement, both Men and women of the main groups, and these differences statistically significant (p <0.001). The above is confirmed by the data of (Adel et al 2019;Mokhtar et al 2019;Saddek et al 2020), according to which it was found that during physical exertion, muscle hypertrophy occurs as a result of adaptive-trophic influence (Mukund et Subramaniam 2020;Teplov 1982), which is characterized by an increase in thickness and denser packaging of contractile elements of muscle fiber (Haun et al 2019;Narici et al 1996). Thus, studies (Annesi et al 2005;Belkadi et al 2019;Krivoruchko et al 2018a;Masliak et Mameshina 2018a) indicate that the introduction of functional exercises in the main part of the lesson contributed to a significant improvement in strength abilities of high school students.…”
Section: Discussionsupporting
confidence: 80%
“…A number of scientists pay considerable attention to the issue optimization of the content of physical education lessons (Masliak et al 2019;Masliak et Mameshina 2018b;Petrova 2021;Varea et al 2021;Voloshina et al 2018). Numerous studies have identified the positive effects of various types of motor activities for the physical fitness of students of different ages (Belkadi et al 2015;Fedewa et Ahn 2011;Mokhtar et al 2019;Seefeldt, Malina, et Clark 2002;Sibley et Etnier 2003;Strong et al 2005). Thus, Vlasova (2017) found an improvement in the level of physical fitness of junior schoolchildren under the influence of fitball-aerobics; Krivoruchko (2018) established a positive dynamics of indicators of the level of speed development under the influence cheerleading exercises for schoolchildren of 5th-6th grades; (Granacher et al 2011;Hsieh et al 2017;Root et al 2019;Yacine et al 2020) found that under the influence of athletic gymnastics classes is reflected the tendency to improve the data of physical fitness in high school students.…”
Section: Introductionmentioning
confidence: 99%
“…there are a considering changes in level indicators development of the maximum dynamic force of abdominal muscles the press, found mainly a significant improvement, both Men and women of the main groups, and these differences statistically significant (p <0.001). The above is confirmed by the data of (Adel et al, 2019;Mokhtar et al, 2019;Saddek et al, 2020), according to which it was found that during physical exertion, muscle hypertrophy occurs as a result of adaptive-trophic influence (Mukund & Subramaniam, 2020;Teplov, 1982), which is characterized by an increase in thickness and denser packaging of contractile elements of muscle fiber (Haun et al, 2019;Narici et al, 1996). Thus, studies (Annesi, Westcott, Faigenbaum, & Unruh, 2005;Belkadi et al, 2019;Krivoruchko et al, 2018;I.…”
Section: Discussionmentioning
confidence: 60%
“…The collection was performed over a period of 30s' for each hand, at a frequency of 1000 Hz, with a signal being issued on a computer screen (Vassin Zenati, Belkadi, & Benbernou, 2021), indicating for the subject to press the dynamometer until another signal is issued, to stop pressing the dynamometer (Bassey, & Short, 1990;Hsu et al, 2011). All volunteers were instructed to perform the grip as quickly as possible, and with as much force as possible, as soon as they observed the visual signal (Hilty, Jäncke, Luechinger, Boutellier, & Lutz, 2011; Mohammed, Bachir, Eddine, & Adel, 2018; Mokhtar et al, 2019). During collection, the subjects did not receive visual feedback and received verbal encouragement from the evaluator.…”
Section: Methodsmentioning
confidence: 99%